A vegetation record based on charcoal analysis from Border Cave, KwaZulu-Natal, South Africa, ∼227 000 to ∼44 000 years ago. (1st October 2022) - Lennox, Sandra; Backwell, Lucinda; d'Errico, Francesco; Wadley, Lyn
Abstract: Border Cave is a key Middle Stone Age (MSA) site in southern Africa, with a 4 m-deep sedimentary sequence that dates from more than 227 000 (227 ka) to 44 ka ago. Lithic assemblages vary considerably during this period and artefacts made from organic materials become common at the end of the MSA sequence. Here we describe charcoal from the 10 members that comprise the stratigraphic sequence. Anatomical features of charcoal were studied by means of reflected light microscopy, the use of the International Association of Wood Anatomists code and modern wood charcoal reference collections. Most woody plants represented by charcoal at the site are evergreen trees. Indicator plants from bushveld and open woodland taxa were most common in Member 6 BS (>227 ka) and Member 5 WA (∼227 ka). Moist forest was most common in Members 5 BS (∼161–144 ka) and 4 WA (∼168–113 ka), while Member 1 RGBS (∼74 ka) had a combination of bushveld and moist forest. At about 64 ka, dry bushveld predominated, while in Members 3 BS (72–56 ka) and 2 WA (∼60 ka) moist forest was the predominant vegetation type. Member 2 BS.UP (49–44 ka) mostly included bushveld and moist forest patches, while Member 1 WA (∼43 ka) was predominantly dry bushveld. The Border Cave occupations seem to have taken place in drier conditions than those at present. The driest members were 5 BS, 4 WA, 1 RGBS and 3 WA, followed by Members 2 BS and 1 WA. Member 3 BS was only slightly drier than present, while Member 2 WA was moderately drier than present. The past vegetation is similar to the modern vegetation profile and there appears to have been remarkable stability through time, suggesting that cultural changes in the sequence may not be linked to environmental change. Highlights: Charcoal was identified from the 10 members that comprise the stratigraphic sequence. The occupations seem to have taken place in drier conditions than those at present. The past vegetation is similar to the modern vegetation profile. There appears to have been remarkable stability through time. Seemingly, cultural changes in the sequence may not be linked to environmental change.